Vitamin D Receptor Activators and Clinical Outcomes in Chronic Kidney Disease - Luciana Gravellone; Maria Antonietta Rizzo; Valentina Martina; Nicoletta Mezzina; Anna Regalia; Maurizio Gallieni (International Journal of Nephrology)
Vitamin D deficiency appears to be an underestimated risk factor for cardiovascular disease in patients with chronic kidney disease. Evidence from both basic science and clinical studies supports the possible protective role of vitamin D beyond its effect on mineral metabolism. Toxicity of pharmacologic doses of active vitamin D metabolites, in particular calcitriol, is mainly due to the possibility of positive calcium and phosphorus balance. Therefore, vitamin D analogs have been developed, which suppress PTH secretion and synthesis with reduced calcemic and phosphatemic effects. Observational studies suggest that in hemodialysis patients the use of a vitamin D receptor (VDR) activator, such as calcitriol, doxercalciferol, paricalcitol, or alfacalcidol, is associated with a reduced mortality when compared with nonusers of any VDR activator. In this article the existing literature on the topic is reviewed, although a more robust answer to the question of whether or not VDR activators have beneficial effects in hemodialysis patients will hopefully come from a randomized controlled trial.